Risk factors associated with the trajectories of mothers' psychological distress across the postnatal and early parenting period - Cooklin, A R; Giallo, Rebecca; Nicholson, Jan (My University, 2013)
Women are at increased risk of psychological distress in the first year postpartum. Few studies have examined the course, persistence and associated risk factors of distress beyond this time. The aims of the study were to: a.Report on the course of distress symptoms over the early parenting period (6-7 years postpartum); b.Identify distinct groups (classes) of women defined by their trajectory of symptoms over time; and c.Identify antenatal and early postnatal risk factors associated with persistent symptoms. Data from 4879 women participating in the Longitudinal Study of Australian Children were analysed. Latent growth class analysis was conducted to identify classes defined by distinct trajectories of distress symptoms, and logistic regression conducted to identify risk factors associated with class membership. For the overall sample, distress symptoms were highest during the first year postpartum and then gradually decreased across the early parenting period. Two distinct classes were identified with the majority of women (84%) reporting minimal distress symptoms over time, and 16% experiencing persistently high symptoms. Early risk factors for persistent distress symptoms were: Younger maternal age; Being from a non-English speaking background; Not completing high school; Having a past history of depression; Antidepressant use during pregnancy; Child development problems; Lower parental self-efficacy; Poor relationship quality; and More stressful life events. This research sheds light on the early risk factors that may predispose women to enduring symptoms of psychological distress across the early parenting period, offering opportunity for early identification and targeted early intervention.
Keywords: Health -- Mental; Families -- Mothers; Families and relationships; Health and wellbeing; Health; Families; Mental; Mothers; Health and wellbeing; Families and relationships